2012
DOI: 10.1180/minmag.2012.076.3.06
|View full text |Cite
|
Sign up to set email alerts
|

Chevkinite-group minerals from Russia and Mongolia: new compositional data from metasomatites and ore deposits

Abstract: Electron-microprobe analyses of Russian and Mongolian chevkinite-group minerals from little-known host lithologies, including various metasomatic rocks, quartzolites and an apatite deposit, are presented. The mineral species analysed include chevkinite-(Ce), perrierite-(Ce), polyakovite-(Ce) and Sr- and Zr-rich perrierite-(Ce). Compositional variation in the Sr-rich members of the group is broadly represented by the exchange vector (Fe + Mn + Al + REE) ↔ (Ca + Sr + Ti + Zr). Despite the varied parageneses, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
(44 reference statements)
1
15
0
3
Order By: Relevance
“…2b, are presented in Table 1, and supplemented in Supplementary Table 1a by five analyses from Macdonald et al (2012). The phase has been classified as chevkinite-(Ce) using the empirical discriminant of Macdonald et al (2009) (Fig.…”
Section: Mineral Compositionsmentioning
confidence: 99%
“…2b, are presented in Table 1, and supplemented in Supplementary Table 1a by five analyses from Macdonald et al (2012). The phase has been classified as chevkinite-(Ce) using the empirical discriminant of Macdonald et al (2009) (Fig.…”
Section: Mineral Compositionsmentioning
confidence: 99%
“…In Figure 3b, chevkinite-(Ce) mantles ilmenite, presumably in a reaction relationship. Figure 3a also depicts a reaction relationship, this time of chevkinite-(Ce) to allanite-(Ce) (see more details in Macdonald et al 2012).…”
Section: Difficulties Of Recognitionmentioning
confidence: 98%
“…The line of discrimination has been modified slightly in subsequent compilations Macdonald et al 2009Macdonald et al , 2012 but has been found to be valid. In c/p from mafic samples, FeO* ranges from ~6.5 to 10.5 wt% and CaO from 3.4 to 7.4 wt%.…”
Section: Chevkinite or Perrieritementioning
confidence: 99%
“…Both chevkinite-(Ce) and perrierite-(Ce) are found in a wide range of rock types (Macdonald and Belkin 2002 and references therein), including intrusive and volcanic igneous rocks Troll et al 2003;Jiang 2006;Vlach and Gualda 2007;Carlier and Lorand 2008;Prol-Ledesma et al 2012;Macdonald et al 2013), metasomatized or hydrothermal rocks such as fenites and ore deposits (Macdonald et al 2012), and metamorphic rocks including granulite facies gneisses ) and metacarbonates ). Chevkinite-(Ce) occurs mainly in syenites, alkaline to peralkaline granites and rhyolites, and fenites whereas perrierite-(Ce) is more common in metaluminous felsic igneous rocks.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation